Examining Mechanisms of Personality Maturation: The Impact of Life Satisfaction on the Development of the Big Five Personality Traits. (March 2013) - Specht, Jule; Egloff, Boris; Schmukle, Stefan C.
Individuals are expected to mature with increasing age, but it is not yet fully understood which factors contribute to this maturation process. Using data of a representative sample of Germans ( N = 14, 718) who gave information about their Big Five personality traits twice over a period of 4 years, the authors identified satisfaction with life, which was reported yearly, as an important variable for explaining mechanisms and interindividual differences in personality maturation. Dual latent change models suggest that more satisfied (compared to less satisfied) individuals experience more positive changes in Emotional Stability, Agreeableness, and Conscientiousness and that positive changes in life satisfaction are associated with positive changes in personality. Furthermore, maturation processes were examined for individuals who faced a social role transition, namely, marriage, birth of a child, or entering the job market. Again, differential effects highlight the importance of life satisfaction for personality maturation.